Hillforts, warfare and society in Bronze Age Ireland - O'Brien, William, (Archaeopress Publishing Ltd, 2017)
This project studies hillforts in relation to warfare and conflict in Bronze Age Ireland. It combines remote sensing and GIS-based landscape analysis with conventional archaeological survey to investigate ten prehistoric hillforts across southern Ireland.